An observational study of trait and state fatigue, and their relation to cognitive fatigability and saccade performance - Marika C Möller; Jan Johansson; Giedre Matuseviciene; Tony Pansell; Catharina Nygren Deboussard (Concussion)
Aim: Different fatigue measurements and their relation to saccadic functions were investigated in 15 patients with a mild traumatic brain injury (mTBI) and 15 orthopedic controls. Materials & methods: State fatigue was measured with the Fatigue Severity Scale and trait fatigue with the question on fatigue in the Rivermead Post Concussion Questionnaire and fatigability as decreased performance over time on a neuropsychological measure. Results: Patients with an mTBI scored significantly higher in state fatigue and showed more fatigability compared with the orthopedic controls. Among patients with mTBI, state fatigue correlated with prosaccade latency and cognitive fatigability, while trait fatigue correlated with anxiety and antisaccade latency and variability. Conclusion: This pilot study indicates that saccade measurements might, in the future, be useful in the understanding of fatigue and in the search for prognostic factors after mTBI.